A torcida "precisa e imparcial" : Isto É, Veja e o Plano Cruzado - Soares, Rafael Fortes (2007)
This dissertation analyses the coverage of Cruzado Economic Plan over Istoé and Veja magazines. Launched on February 1986 by president José Sarney, it lasted until November, and it s main goal was to beat inflation. To a great extent, the Plan s success was due to the massive engagement of Brazilians. In such context, journalism performed a key role: on one hand, it cleared up the new economic rules to the astonished population; on the other hand, it had an active and relevant participation in mobilizing citizens around the Plan. The main objective of this work is to investigate the way journalism acted in Cruzado Plan coverage, for it established a new paradigm in Brazilian journalism. While covering Cruzado Plan, the press not only answerd questions given by the population, but it renegotiated its own place in Brazilian society. Due to economic journalism, it achieved a new status in its relation with the public. The analysis of the role played by journalism is done in two forms: considering the coverage itself; and trying to understand how this coverage was important in redefinition of journalism role in Brazilian new democractic order. The analysis is based on notions of framing and authority, favouring the political and cultural aspects of journalism role. How did journalism cover the Pla n? Which role did it vindicate to itself on and from that coverage? In which ways was the participation of the fiscais do Sarney [Sarney s inspectors] related by the magazines to citizenship and consumption? What implications can the role magazine s played on that coverage bring to the reflection over the rule of the press in Brazilian democracy?